Performance and scientific mapping of heutagogy publication from 2005 to 2024: A bibliometric analysis - Kardiyem; Bandi; Susilaningsih; Fery Setyowibowo (Social Sciences and Humanities Open)
This study was initiated to address the limited bibliometric analyses on heutagogy, despite its growing prominence in higher education as a learner-centered, self-determined approach. As the field gains momentum, understanding its research landscape is essential for guiding future pedagogical practices and scholarship. We conducted a bibliometric review of 290 publications from 2005 to 2024 indexed in the Scopus database, applying PRISMA guidelines and defined inclusion and exclusion criteria. VOSviewer was used to analyze citation networks, co-authorship patterns, and keyword co-occurrences. Findings show a significant increase in publications, peaking in 2020, with Blaschke identified as the most cited author and Cochrane as the most prolific. Auckland University led institutional contributions. The research spans disciplines such as education, computer science, and business, with thematic focuses on educational technology, lifelong learning, and 21st-century skills. However, collaboration remains largely regional, indicating opportunities for broader international engagement. The review highlights heutagogy's growing impact on flexible and technology-enhanced learning environments. These insights have practical implications for curriculum development, instructional design, and educational policy. Conclusively, heutagogy is poised to play a transformative role in higher education, particularly in promoting autonomy, adaptability, and lifelong learning. Future research should expand global collaboration heutagogical practices.